Supportive Chinese supervisor, innovative international students: a social exchange theory perspective - Fan, Luo; Mahmood, Monowar; Uddin, Md. Aftab (Asia Pacific education review, 2019)
This study investigates the impact of supervisor support on research innovation pursuit among international doctoral students in China. A total of 120 international doctoral students’ responses were employed through random sampling from the three business schools of Chinese public universities. The data were analyzed using the partial least squares technique, a second-generation statistical software package for structural equation modeling. The results revealed that supervisor support significantly affects students’ research innovation endeavors. The study also suggests that supportive supervision is necessary for fostering citizenship behavior, creativity and innovation pursuit among international doctoral students. The findings of this pioneering study will help higher education administrators, and policymakers revisit existing doctoral program management and deliveries processes and encourage academic supervisors to modify guidance and mentoring procedures for doctoral students.